Pengaruh Literasi Keuangan terhadap Perilaku Keuangan dengan Sikap Keuangan Sebagai Variabel Intervening Mahasiswa Fakultas Ekonomi Universitas Sriwijaya - Sendi Marcelleo Arkan, Sendi Marcelleo Arkan; Marlina Widiyanti, Marlina Widiyanti; Fida Muthia, Fida Muthia; Isni Andriana, Isni Andriana (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this study was to find out whether financial literacy has an influence on students' financial behavior with financial attitudes as an intervening or mediating variable. The sampling technique used purposive sampling so that 100 samples were obtained which were students of the Faculty of Economics, Sriwijaya University. This research is a descriptive research with primary data. Data processing was carried out using the Partial Least Square analysis model with the help of WarpPLS 7.0 for windows. This study uses a measurement model (Inner model) and a Structural model (Outer model). The results of the hypothesis test show that (1) Financial Literacy has a direct effect on Financial Behavior, (2) Financial Literacy has a direct effect on Financial Attitudes, (3) Financial Attitudes has a direct effect on Financial Behavior, (4) Financial Attitudes are proven to fully mediate the effect of Financial Literacy on Financial Behavior.